SALBEC – A python library and GUI application to calculate the diurnal variation of the soil albedo - Jasiewicz, Jarosław; Cierniewski, Jerzy (Quaestiones Geographicae, 2021)
This study presents the SALBEC – Soil ALBEdo Calculator – a Python library and Graphical User Interface designed to predict the diurnal variation of the clear-sky albedo based on the soil surface properties. Such predictions are becoming more and more necessary with the increasing role of remote measurements. The software uses the following input parameters: the soil spectrum, soil roughness, day of the year (DOY) and sample location. It returns the diurnal albedo variation and, as a unique feature, optimal observation time in the form of tables and graphs as out-puts. Models created with the SALBEC were compared with the data acquired under near clear-sky conditions. The comparison shows that the differences between the models and measured data do not exceed the variation of input parameters. The software is directed towards scientists and professionals who require precise estimations of the albedo of soils for different field observation times. Our software is issued as free and open source software (FOSS) and is publicly available at https://github.com/jarekj71/salbec.